Big Nate : silent but deadly - Peirce, Lincoln (Andrews McMeel Publishing, 2018)
Collects a series of comic strips featuring Big Nate and his antics in middle school with his teachers and classmates, such as showing a detention rookie the ropes, trying to win Student of the Month Award, and sets up his gig as the "Great Nose-ini" who can identify anything by just a smell.